Arthroscopic assisted versus all arthroscopic rotator cuff repair at mid-term follow up. - Adil Bashir, Yawar Haider, Munir Farooq, Berjina Farooq Naqshi, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Among the most common causes of the shoulder pain and disability are the rotator cuff tears. The repair of rotator cuff